Evaluation of Top Journals and Authors in Behavioral Economics: A Bibliometric Approach - Supriandi, Supriandi; Devi, Erwina Kartika; v, Daud; Munip, Al; Abnaina, Elma (West Science Journal Economic and Entrepreneurship, 2024)
Behavioral economics has become an essential subfield within economics, integrating psychological insights to better understand decision-making processes. This study conducts a comprehensive bibliometric analysis to evaluate the evolution of behavioral economics, identify key research themes, and map the contributions of influential authors. Using data sourced from the Google Scholar database, the study analyzes publication trends, co-authorship networks, and the temporal development of research areas. The findings reveal that core concepts such as behavioral finance, public policy, and experimental economics continue to dominate the field, while emerging areas like consumer behavior and insurance indicate new research directions. The co-authorship analysis highlights the importance of collaboration among scholars in shaping the field's development. These insights provide valuable implications for researchers, educators, policymakers, and funding bodies in guiding future research, curriculum development, and resource allocation. This study contributes to a deeper understanding of the intellectual structure and trajectory of behavioral economics.